EXTH-54. Bcl-2/Bcl-xL INHIBITION SYNERGISTICALLY ENHANCES THE ANTI-NEOPLASTIC ACTIVITY OF CUSP9 AGAINST GLIOBLASTOMA CELLS IN VITRO. (5th November 2018) - Halatsch, Marc-Eric; Kast, Richard Eric; Dwucet, Annika; Wirtz, Christian Rainer; Siegelin, Markus; Karpel-Massler, Georg
Abstract: OBJECTIVE: Repurposing represents a promising approach to safely accelerate the clinical application of therapeutics with anti-cancer activity. In this study, we examined whether inhibition of the anti-apoptotic Bcl-2 family proteins Bcl-2 and Bcl-xL enhances the biological effects of the repurposed CUSP9 regimen in an in vitro setting of glioblastoma. METHODS: We applied MTT assays to assess cellular proliferation. Annexin V/PI and TMRE staining were used to examine apoptosis. Western blotting, RT-PCR and specific knockdown experiments using siRNA were employed to examine molecular mechanisms of action. RESULTS: Bcl-2/Bcl-xL inhibition by the BH3 mimetic ABT263, yielded synergistic anti-proliferative effects across a wide panel of established and primary cultured glioblastoma cells when combined with CUSP9 which had been reduced to only one tenth of its original concentration (CUSP9 1/10). The combination treatment also led to enhanced apoptosis with loss of mitochondrial membrane potential and activation of caspases. On the molecular level, CUSP9 1/10 counteracted ABT263-mediated upregulation of Mcl-1. Silencing of Mcl-1 enhanced ABT263-mediated apoptosis, indicating that Mcl-1 is crucial for the induction of cell death conveyed by the combination treatment. Levels of Mcl-1 mRNA were not decreased following combination therapy, and co-treatment with cycloheximide showed reduced protein stability, pointing towards a post-translational mechanism of action. CONCLUSION: These data suggest that Bcl-2/Bcl-xL inhibition enhances the susceptibility of glioblastoma cells towards CUSP9, allowing dramatic dose reduction and potentially decreased toxicity when applied clinically. A clinical trial involving the original CUSP doses (CUSP9v3) is currently ongoing in our institution (NCT02770378). The Bcl-2/Bcl-xL inhibitor ABT263 is in clinical trials and might represent a valuable adjunct to the original CUSP.